2017
DOI: 10.1186/s13104-017-2572-2
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal regenerative therapy with enamel matrix derivative in the treatment of intrabony defects: a prospective 2-year study

Abstract: ObjectiveTo date, enamel matrix derivative (EMD) has been considered to be one of the few biomaterials for clinical use capable of demonstrating true periodontal regeneration. The aim of this two-center prospective clinical study was to evaluate 2-year outcome of periodontal regenerative therapy using EMD in the treatment of intrabony defects, performed as an ‘advanced medical treatment’ under the national healthcare system in Japan.ResultsPatients with chronic periodontitis who have completed initial periodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 22 publications
5
20
0
Order By: Relevance
“…Heijl et al observed a mild increase in bone fill until 36 months 9) . In the present case, also, a significant increase was observed in bone fill between 1Y and 2Y, which supports earlier findings 9,22) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Heijl et al observed a mild increase in bone fill until 36 months 9) . In the present case, also, a significant increase was observed in bone fill between 1Y and 2Y, which supports earlier findings 9,22) .…”
Section: Discussionsupporting
confidence: 93%
“…A number of studies have investigated the effect of periodontal regenerative therapies, and the results have been favorable. One such therapy, which uses enamel matrix derivative (EMD; Emdogain ® Gel, Straumann, Basel, Switzerland), has now been used for over 20 years, and various degrees of clinical resolution have been reported with this approach 8,9,17,22,23) .…”
Section: Introductionmentioning
confidence: 99%
“…In order to support regeneration of the injured periodontium grafting materials might be inserted [16]. These include a whole range of materials such as barrier membranes, autografts, demineralized and freeze-dried bone allografts, bovine-derived xenografts and the combination of membranes and filler substances as well as the local application of growth factors such as Emdogain® or GEM 21S® [15,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…These therapies result in an overall improvement to periodontal tissue health. However clinical results have limited predictability due to being sensitive to patient behaviour, surgical approach and periodontal defect morphology, favouring narrow, confined intrabony defects [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%